THE DEVELOPMENT OF 3D PRINTING MODIFICATION OF LIQUID HANDLING SYSTEM CONCEPT FOR PIPETTING SYSTEM PROCESS IN THE MEDICAL AREA - Abdi, Ferly Isnomo; Sakti, Arya Mahendra; Wulandari, Diah; Utama, Firman Yasa; Puspitasari, Dewi; Manggalasari, Lena Citra (DIVERSITY Logic Journal Multidisciplinary, 2023)
Background. The development of electromedical technology in the healthcare field is increasing. However, the measurement of liquid samples in the pipetting process is still done manually which makes it highly contaminated from human hands. A Liquid Handling System (LHS) is a device used to automatically transfer fluids to prevent contamination. 3D Printing is a tool used to create creative design objects using filament material. The mechanism of this tool is similar to that of a liquid handling system but is simpler and has a smaller capacity. In the future, Research Purpose. To determine 3D printing modification of liquid handling system for pipetting system process in the medical area. Research Method. This research uses the research and development (R&D) method by designing and constructing a Prototype Liquid Handling System with a modified 3D Printing 3-axis, placing measuring cups and sample tubes, and designing G-Code programs and servo motor coding to test the capabilities of the designed Prototype Liquid Handling System. Findings. Based on the functional test results of the liquid handling system using NaCl solution, the pipetting results were 0.82 ml with a processing time of 5.6 seconds. The electromedical device has a percentage error rate of 2.4% with a pulling force of 6.56 N and an injection pressure of 8.44 Pa. Conclusion. This electromedical device will be able to automatically process extraction fluids or pipetting processes with high accuracy.